Pengaruh Market Growth dan Oppeness Terhadap Foreign Direct Investment Tahun 2000 - 2021: Studi Kasus 8 Negara Asia - Vinandri Hapsari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Foreign Direct Investment (FDI) is the most potential source of foreign financing compared to other sources which can result in capital gaps. Conceptually, investors in determining which country to invest their capital in are influenced by the conditions of the recipient country (pull factor). Apart from that, there are other factors that influence investors' interest in investing their capital in the destination country, namely the strategic conditions of investment (push factors). This researcher used descriptive and verification research methods. The analysis results from panel data show that the magnitude of the influence of market growth and economic openness on foreign direct investment (FDI) in 8 Asian countries is 66.79%, and the remaining 33.21% is influenced by other variables outside the research variables.